2020
DOI: 10.1155/2020/9809632
|View full text |Cite
|
Sign up to set email alerts
|

The Role of circRNA‐SETD2/miR‐519a/PTEN Axis in Fetal Birth Weight through Regulating Trophoblast Proliferation

Abstract: Abnormal birth weight is the one of the major causes of adulthood diseases such as obesity, metabolic syndrome, cardiovascular disease, type 2 diabetes, and hypertension. Accumulating evidence has suggested that the placental trophoblast is one of the most important reasons that influence birth weight. Our previous study showed that miR-519a are correlated with low fetal birth weight through regulating trophoblast proliferation. To further clarify the detailed mechanisms on how it is regulated, we screened the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…19 , 33 , 34 , 35 , 36 Increasing studies showed that circRNAs involved in the development of many diseases including cancers, neurological diseases, congenital diseases, intervertebral disc degeneration and endocrine diseases. 37 , 38 , 39 , 40 , 41 , 42 , 43 Recently, studies indicated that circRNAs also play important roles in osteoporosis. 44 …”
Section: Introductionmentioning
confidence: 99%
“…19 , 33 , 34 , 35 , 36 Increasing studies showed that circRNAs involved in the development of many diseases including cancers, neurological diseases, congenital diseases, intervertebral disc degeneration and endocrine diseases. 37 , 38 , 39 , 40 , 41 , 42 , 43 Recently, studies indicated that circRNAs also play important roles in osteoporosis. 44 …”
Section: Introductionmentioning
confidence: 99%
“…However, circRNAs are mainly considered as miRNA inhibitors (or “sponges”) ( 164 ), and then regulate gene expression at post-transcriptional levels. So they explored the downstream target of circRNA-SETD2 in cell experiment, verified that the circRNA-SETD2/miR-519a/PTEN axis ( 163 ). And miR-519a has been mentioned previously to be involved in regulating birth weight.…”
Section: Role Of Ncrnas In Abnormal Birth Weight In Offspringmentioning
confidence: 90%
“…Of note, in 2020, instead of investigating the LBW groups, Wang et al ( 163 ) studied miRNAs in the placenta of macrosomia, finding that circRNA-SETD2 (hsa-circRNA-103345) is upregulated. Compared with miRNAs, the mechanism of circRNAs is not fully understood and there are some controversies.…”
Section: Role Of Ncrnas In Abnormal Birth Weight In Offspringmentioning
confidence: 99%
“…Most circRNAs can perform specific dynamic regulation during embryonic development and are mainly involved in the regulation of material metabolic pathways in early embryonic development [15]. 3 BioMed Research International detect the expression of circRNAs [14]. They found that the sow's quantity and complexity of circRNAs expression were most obvious in the cortex at the 60th day of pregnancy of the 13,854 expressed genes detected; 2,195 genes expressed 4,634 unique circRNAs; In addition, Hirotsu et al found that the expression of circRIMS2 in the embryonic pig cortex reached a peak during development, suggesting that cir-cRNAs are one of the major factors regulating mammalian embryonic brain development [51].…”
Section: Circrnas Regulate Fetal Development In Livestockmentioning
confidence: 99%
“…In addition, studies have shown that circRNAs can regulate fetal development, and their expression is the most abundant and complex in the cerebral cortex on the 60th day of pregnancy [14][15][16]. Studies have shown that there are 10,032 circRNAs in human ocytes and embryos, a small portion of which are maternally expressed, and most of the circRNAs have been shown to be related to animal embryo development [17].…”
Section: Introductionmentioning
confidence: 99%